2008
DOI: 10.1159/000132691
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Incontinence in the 12-Month Postpartum Period and Related Risk Factors in Turkey

Abstract: Aim: The purpose of this study is to determine the prevalence of urinary incontinence in the 12-month postpartum period and the risk factors related to this condition. Methods: The research is a cross-sectional study of 1,749 first-year postpartum women living in the metropolis of Konya and presenting at seven city health centers. The statistical methods used were the χ2, the Student’s t test and logistic regression analysis. Results: Of the women in the study who were in their 12-month postpartum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 64 publications
(54 reference statements)
2
23
0
2
Order By: Relevance
“…In the literature, it is remarkable that the results of the studies investigating the correlation between big baby birth and UI are contradictory. While a correlation was found between big baby birth and UI in some studies, no significant correlation was found in some other studies similar to results of the present study …”
Section: Discussionsupporting
confidence: 82%
“…In the literature, it is remarkable that the results of the studies investigating the correlation between big baby birth and UI are contradictory. While a correlation was found between big baby birth and UI in some studies, no significant correlation was found in some other studies similar to results of the present study …”
Section: Discussionsupporting
confidence: 82%
“…After childbirth, the reported prevalence of LUTS declines rapidly within 6 months. Numerous risk factors for postpartum LUTS have been widely studied; however, most studies investigating the relationship between pregnancy/delivery and LUTS have follow‐up periods of ≤1 year . The long‐term persistence of LUTS following childbirth, however, is not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the percentage of women who claimed experiencing urinary incontinence, during the postpartum period, was higher compared to the studies conducted in Denmark (23.4%) (10) , Italy (20.3%) (13) and Turkey (19.5%) (20) .…”
Section: Discussionmentioning
confidence: 55%